Emergence of monkeypox virus: a public health threat - Mrudula, Alla Sai Santhosha; Alla, Deekshitha; Muneesh, Seepana; Sireesha, Thippana; Durga Bhavani, Baddi; Vandana, Kanakam; Chaturya, Gopu (International Journal of Advances in Medicine, 2022)
The human monkeypox virus is a zoonotic infection that is closely related to smallpox virus. It more commonly exists in forested habitats of western and central Africa. In the recent outbreak of the monkeypox virus, the total number of positive cases escalated to 32,760 and 12 deaths were reported so far. With rodents being primary reservoirs, the virus spreads through animals, fomites, respiratory droplets and, direct contact. It typically presents as a vesiculo-pustular rash along with fever, headache, malaise and chills. Taking this clinical spectrum into consideration, differential diagnosis to rule out smallpox is very much significant. Though there are no licensed therapies for monkeypox, treatment regimens and vaccination for small pox can also be used for monkeypox. Effective prevention relies on avoiding contact and limiting respiratory exposure with the infected patients by following standard precautions. This review article gives an insight into epidemiology, clinical presentation, diagnosis, transmission, vaccination, and prevention of infection.